Conserved G-Quadruplex Motifs in Gene Promoter Region Reveals a Novel Therapeutic Approach to Target Multi-Drug Resistance Klebsiella pneumoniae - Shankar, Uma; Jain, Neha; Mishra, Subodh Kumar; Sharma, Tarun Kumar; Kumar, Amit (Frontiers in Microbiology, 2020)
An opportunistic pathogen, Klebsiella pneumoniae is known to cause life-threating nosocomial infection with a high rate of morbidity and mortality. Evolutions of multi-drug resistant and hypervirulent strains of Klebsiella pneumoniae makes the situation more worse. Currently, there is no incisive drug molecule available for drug resistant hypervirulent Klebsiella pneumoniae infection that emphasizes the need for identification of novel and more promising drug targets in Klebsiella pneumoniae. Recently, various non-canonical structures of nucleic acids especially G-quadruplex (G4) motifs have been identified as potential therapeutic targets against several human pathogenic bacteria and viruses including Mycobacterium tuberculosis, Streptococcus pneumoniae, HIV, Ebola and Nipah. Therefore, in present study we screened the Klebsiella pneumoniae genomes for identification of evolutionary conserved G-quadruplex structure forming motifs as promising anti-bacterial drug target. Bioinformatics analysis revealed the presence of 6 highly conserved G-quadruplex motifs in the promoter region of 5 essential genes that play a critical role in nutrient transport and metabolism. Biophysical studies showed the formation of G-quadruplex structure by these conserved motifs. Circular Dichroism melting analysis showed the stabilization of these G4 motifs by a well-known G4 stabilizing agent BRACO-19. The stabilization of these motifs by BRACO-19 was also able to stops the primer extension process which is an essential phenomenon for expression of the G4 harboring gene. The addition of G-quadruplex specific ligand in low micromolar range was observed to be lethal to the bacterial growth and negatively controlled the expression of the G4 harboring genes via G-quadruplex structure stabilization. These observations strengthen the formation of G-quadruplex structures by predicted G4 motif in vivo which can be stabilized by G4 ligands like BRACO-19. This stabilization of G-quadruplex structures can attenuate the expression of G-quadruplex harbouring essential genes and thus play a critical role in the regulation of gene expression. Thus taking all given result in consideration, for the first time, this study showed the new therapeutic avenue for combating Klebsiella pneumoniae infection by characterizing the conserved G-quadruplex motifs as promising therapeutic targets.